THE CORRELATION BETWEEN WITS AND ANB CEPHALOMETRIC LANDMARKS IN ORTHODONTIC PATEINTS - Jan, Abdullah; Bangash, Azhar Ali; Shinwari, Saad (Pakistan Armed Forces Medical Journal, 2017)
Objective: To correlate cephalometric values of ANB angle and Wits appraisal in patients reporting to AFID. Study Design: Cross sectional, comparative study. Place and Duration of Study: The study was carried out in the Department of Orthodontics at AFID Rawalpindi. ANB and Wits values from Lateral cephalograms of patients, from Dec 2014 till May 2015 were recorded. Material and Methods: On the basis of inclusion criteria; out of a total of 200 lateral cephalograms, 161 Lateral Cephalograms were selected. Their ANB values and wits values were recorded. Correlation was found by Pearson correlation test. Bivariate analysis was done. A p-value of ≤0.05 was considered to be statistically significant. SPSS 22 was used for statistical analysis. Results: Our results showed that 34.8% of the patients were males and 65.2% were females. Regarding class of malocclusion (I, II and III); 41% were class I, 44.1 were Class II and 14.9% were class III. The age range was from 9 to 33 years with a mean of 14.46 years. Regarding the correlation, bivariate analysis showed that the ANB and Wits were significantly correlated with an “r” value of 0.469 and a p-value of 0.00 which was statistically significant. Conclusion: ANB and Wits are significantly correlated.